Teaching business in Malaysia and the use of PBL to nurture students’ critical thinking: a case study of Sultan Idris Education University - Mohd Nazir Md. Zabit,; Eleni Karagiannidou,; Tirzah Zubeidah Zachariah @ Omar, (School of Social, Development and Environmental Studies, Faculty of Social Science and Humanities, Universiti Kebangsaan Malaysia, 2016)
PBL gained considerable attention from teaching and learning theorists, educators, policy makers and researchers, as learning is thought to involve not only knowing how to do things effectively but more importantly, the ability to deal with novelty and to grow our capacity in order to adapt, select and shape our interactions with the environment.The aims of Problem-Based Learning (PBL) is to foster students’ active learning, as opposed to passive learning experiences typically occurring in lectures. This study focused on the PBL methodology and Critical Thinking (CT) skills. It employed a quasi-experimental design, where 45 students undertaking a B. Ed (Economics) at Sultan Idris Education University (UPSI) were randomly assigned as experimental (n=23) and control groups (n=22). The former were instructed using the PBL method while the control group used the traditional learning method. The analysis focused on comparing the PBL with traditional learning groups in respect of their CT skills (Inductive, Deductive, Analysis, Inference and Evaluation and Total CT), as measured by the California Critical Thinking Skills Test. The results showed that there was no significant group difference in overall test scores at pre-test and midintervention test. However, differences were found at post-test with respect to the Inductive and Analysis subscales. Implications of the study relate to the imperative of a whole PBL programme approach to foster and enhance students’ critical thinking rather than by delivery via a single course. In other words, UPSI needs to turn their focus to enquiry-based learning, including PBL, hands-on learning, problem solving skills as well as creative and CT skills.